历史创伤叙事：在新加坡被审查的政治创伤记忆 = The narrative of historical trauma: censored political traumatic memories in Singapore - 姚进顺 Yau, Matthew Jin Shun (Nanyang Technological University, 2023)
新加坡曾经历一段政治历史创伤，但因为涉及事件被视为在挑战国家权威，这段创伤记忆也随之遭受官方压制。这就导致受创者无法向外诉说创伤经历，无奈陷入于历史创伤之中。然而，这段历史却是大众了解新加坡发展的重要元素，有效反映国家历史的完整面貌。对此，本文将以两部纪录片《1987年：阴谋反追溯》和《星国恋》，以及小说《紧急状态》为例，探讨这三部艺术作品是如何透过不同叙事手法以处理这段被官方审查的政治历史创伤，从而赋予受创者叙事创伤的能力。此外，本文希望在分析过程中也能唤醒被国人逐渐淡忘的历史片段，从而一同探讨这段创伤记忆的存在意义。 Singapore had gone through a period of political historical trauma, and those traumatic memories involved were suppressed as they were viewed as an attempt to challenge the official authority. As a result, these trauma victims were unable to share their traumatic experiences with the outside world and were left plunging back into the historical trauma. However, this period is a crucial part of history for the public to understand the development of Singapore, as it effectively reflects the complete picture of the country's history. Therefore, focusing on two documentaries, 1987: Untracing the Conspiracy and To Singapore, with Love, together with the novel State of Emergency, this paper aims to explore how these three artworks handle the state-censored political historical trauma through different narratives, thereby empowering the victims the ability to recount their trauma. In addition, this paper hopes that in the process of analysing, it will also evoke the fragments of history that have been gradually forgotten by Singaporeans, with the aim to discuss the significance of these traumatic memories.